Islamophobia In American Prose: A Contrapuntal Reading Of The Jewel Of Medina, Falling Man And Infidel - Isa, Sadiya Abubakar (2021)
The aftermath of 9/11 attacks saw an outburst of literary publications in America and Europe about Islam and Muslims. Most of these novels reproduced dominant images of Muslims as violent murderers or terrorists and of Islam as a misogynist and an intolerant religion. Thus, America witnessed a surge of Islamophobia to which literature, alongside media and cinema, remain susceptible. A bulk of criticisms that followed situate these novels under Edward Said’s structures of Orientalism, facilitating the argument for their Islamophobic implications. These endeavours have been reproached for using Islamophobia to shield away from critical scrutiny. Said’s theoretical concept of representation is itself criticized for being inconsistent and unrepresentable of itself. Thus, the criteria for locating post-9/11 texts as Islamophobic within the theoretical and analytical construing of Orientalism is problematized. The crux of this study, therefore, is to delimit Islamophobia pertaining to the construct of Orientalism. The research aims to investigate whether or not, and to what extent, there is Islamophobia in the selected American proses, namely Sherry Jones’ The Jewel of Medina (2008), Don DeLillo’s Falling Man (2007) and Ayaan Hirsi Ali’s Infidel (2007). To achieve this underlying objective, the study proposes a model of reading and interpreting the novels, which incorporates Edward Said’s theories of Orientalism and Contrapuntal readings.